Genetic Resistance to Greenbug is Expressed with Higher Contents of Proteins and Non-Structural Carbohydrates in Wheat Substitution Lines - Castro, Ana María (2005)
This paper studied the endogenous levels of reduced, non-reduced, total non-structural carbohydrates, soluble proteins and biomass in aerial and rooting structures of bread wheat, Triticum aestivum (2n=6x=42), in response to aphids, as a first step for understanding the cascade of transductional events that may account for antixenosis, antibiosis and tolerance to greenbug. Up to now, few studies have been made on the relationship between aphid resistance and these traits. A set of wheat intervarietal chromosome substitution lines, with ‘‘Chinese Spring’’ (CS, a greenbug susceptible line) as a recipient and a synthetic wheat (Triticum dicoccum x T tauschii, = [Syn]) as the donor, and both parents were used. Plants were cultivated in hydroponic solutions to the fully expanded 3rd leaf stage. Half of the plants of every genotype were infested 72h with greenbugs, and the remaining uninfested plants were used as controls. Carbohydrate and protein contents and dry matter mass were determined for aerial and root tissues Lines 5A and 6A had lower aerial, root and, consequently, total dry weights in both control and infested plants. These lines have been previously reported to be antixenotic against greenbug and Russian Wheat Aphid (RWA), implying these lines carry genes for constitutive defences. Four substitution lines (1A, 1B, 7B and 7D) showed significant increases in protein content when infested, compared to their controls and to the CS susceptible parent. Considering that these substitution lines have been previously reported to reduce greenbug and RWA fertilities and longevities, the antibiotic resistance to greenbugs may be related to gene expression for enhanced protein levels. Most of the D genome substitution lines showed an increase of total root carbohydrates with the greatest increase in total root and aerial carbohydrates under infestation in the 1D and 6D substitution lines. Since these lines have been reported as being tolerant to greenbug, their highest carbohydrate contents probably protect them against biotic stress by enhancing growth. Greenbug resistance genes have been mapped only on the 1A, 6A, 7A and 7D chromosomes. Nonetheless, it was possible to identify other substitution lines that showed effects in the photosynthesis, the C and N metabolisms in the cascade of transductional signals that account for antixenosis, antibiosis and tolerance to greenbug in wheat